Twin Screw Granulation: An Investigation of the Effect of Barrel Fill Level - Sushma V. Lute; Ranjit M. Dhenge; Agba D. Salman (MDPI AG, 2018)
This paper focuses on investigating the influence of varying barrel fill levels on the mean residence time, granule properties (median size, size distribution, and shape), and tensile strength of tablets. Specific feed load (SFL) (powder feed rate divided by screw speed) and powder feed number (PFN) (i.e., powder mass flow rate divided by the product of screw speed, screw diameter, and the material density in the denominator) were considered as surrogates for the barrel fill level. Two type of powders (lactose and microcrystalline cellulose (MCC)) were granulated separately at varying fill levels at different liquid-to-solid ratios (L/S). It was observed that by controlling the barrel fill level, the granule size, shape, and tablet tensile strength can be maintained at specific L/S. It was also noticed that the mean residence time decreased with increasing fill levels in the case of both lactose and MCC powder. However, it was only found to be related to the change in granule size in case of granulating microcrystalline cellulose at varying fill levels. At very high fill levels, granule size decreased, owing to a limited interaction between MCC powder and liquid at high throughput force and short residence time.